A Six-year ICTC based study on the sociodemographic profile of the HIV infected individuals in North-West Region of India - Perween, Nusrat; Sami, Hiba; Rizvi, Meher; Khan, Parvez A; Raza, Adil; Fatima, Nazish; Khan, Haris M (International Journal of Human and Health Sciences (IJHHS), 2023)
Introduction- It is well recognized that, if left untreated HIV progresses through several stages due to the progression in immunosuppression. The level of immunosuppression is linked directly to the CD4+ T-lymphocyte count as well as to acquisition of opportunistic infections. The data generated in the Integrated Counselling and Testing Centre (ICTC) provides a valuable information pertaining to the demographic epidemiology and clinical profile of the HIV positive patients of that particular region. In this study, we analysed the sociodemographic and clinical profiles of the attendees at the ICTC of a tertiary care hospital over a period of 6 years. Material and Methods- This study included 1205 HIV positive patients who attended ICTC either voluntarily or after being referred by various departments and being tested for their HIV serostatus since January 2014 to December 2019 in the ICTC, JNMCH, Aligarh, U.P. Results- Out of the 32680 attendees, the total HIV positives were 1205 (3.68%), out of which 61.3% were males and 38.4% were females. Majority of the patients (755/1205), belonged to the age group of 20-39 yrs. The pattern of risk behaviour showed that a large percentage (59.9%) of HIV positive patients had a sexual mode of transmission. Most of the HIV Positive patients presented with fever (47.4%), weight loss (46.5%), cough (15.4%), diarrhoea and oral ulcer (8.8%), coinfection of TB (6.8%) whereas 14.4% were asymptomatic. In the Pre ART monitoring, most of the patients (498; 41.3%) had a CD4 Count <200 whereas after 6 months of ART the number of HIV positive patient with CD< 200 decreased to 324; 26.8%. 128 (10.6%) patients died while on ART treatment. Majority (72%) of the patients with unfavourable outcome belonged to WHO Stage 3 and 4. Conclusion- Most of the patients were young and in the sexually active age group. This disease not only results in financial loss to the family but also adds an extra burden of taking the treatment lifelong. The ICTC programme is playing an important role in early diagnosis of HIV and connecting the patients to ART facilities. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S188-S197